PENGARUH PENJUALAN BERSIH TERHADAP LABA PADA PT. PABRIK KERTAS TJIWI KIMIA Tbk - Rafnidar .; Wulandari . (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2020)
This study aims to determine the effect of net sales and profits at PT. TJIWI KIMIA PAPER FACTORY Tbk. The population in this study is the balance sheet financial report data for 29 years (1989-2018) and the study sample for 7 years (2012-2018) with the sampling used is purposive sampling. This research is an associative research using a quantitative approach consisting of secondary data. The process of collecting research data uses library research and documentation. Data analysis techniques used in this study are simple linear regression, correlation, coefficient of determination and hypothesis testing using t-statistic test. The results showed that net sales had no significant effect on profits at PT. TJIWI KIMIA PAPER FACTORY Tbk.